Deconstructing the Gender Hierarchy in the Interpretation of Quran 4:34: A Contextual Hermeneutical Approach from the Perspective of Amina Wadud - Chodijah Asy Syarifah; Fauzan Zenrif; Kuni Nurol Choiriyah (Indonesian Academy of Social and Religious Research (IASRR), 2026)
The interpretation of Quranic Surah An-Nisa: 34 in the classical exegetical tradition has given rise to a gender hierarchy that posits qiwamah as the permanent authority of men over women, an understanding that continues to influence social norms, Islamic family law, and gender relations in Muslim societies to this day. This article aims to deconstruct this hierarchical construct through an integrative, contextual hermeneutic approach, using Amina Wadud's thought as its primary methodological foundation. This study employs a qualitative, library-based research method with three stages of analysis: socio-historical, semantic-linguistic, and intra-textual. The results indicate that the gender hierarchy is formed through four hermeneutical mechanisms: the generalization of particular contexts, the naturalization of social constructs, intra-textual selectivity, and the transmission of the exegetes' androcentrism. A semantic-linguistic analysis of the terms qawwamah, faddhala, nusyuz, and dharaba reveals that the Qur'anic text does not support an absolute gender hierarchy; qawwamah is more accurately understood as a conditional and reciprocal functional responsibility. This study contributes to strengthening the epistemological foundation of inclusive gender exegesis. It offers an integrative hermeneutical model relevant to reforming Islamic family law and religious education in Indonesia.